Transgressing the Border of Gender in Sheeba Shah’s The Other Queen - Bista, Asmita; Rai, Jiwan Kumar (Dristikon: A Multidisciplinary Journal, 2025)
Setting the novel in the rule of the King Rajendra Bir Bikram Shah (1816-1847 BS), Sheeba Shah’s The Other Queen documents the actions and activities of the King Rajendra and his queens Samrajya Laxmi and Rajya Laxmi which resulted on the unbalanced power sharing of the nation. Shah stresses that the main cause behind this is crossing the gender boundary by the King and the Queens as they undermine the stereotyped gender roles and identity. In the novel, the king disobeys to stick to the image of an authoritative valor; so, he appears as subservient coward. Queens are self-confident and powermongers; they deny to perform the roles of submissive and self-sacrificing women. Thus, this article aims to study the reasons that instigate the major characters to defy the conventional gender image and cross the gender border set by the society. It also highlights the consequences faced by the characters for crossing the gender confinement. To address this objective, Butler’s concept of gender performativity has been used as she claims that the ‘performances of gender’ are not natural one; they are imposed to an individual through the social script. She views that an individual creates one’s gender by performing the script repetitively; nevertheless, s/he finds the space even there and repeats the acts differently. Hence, one gets options within those constraints to break them. Moreover, gender is constantly reconstructed in response to socio-political changes. The implication of this article is to find insights in understanding the emergence of power in the Queens that is resulted by the performance of their gender roles. It concludes that characters of Shah’s novel challenge the socially prescribed gender roles and they recurrently cross the gender confinement.